Melatonin reduces melanogenesis by inhibiting the paracrine effects of keratinocytes. Issue 4 (21st January 2023) - Yang, Siyu; Zeng, Hongliang; Jiang, Ling; Fu, Chuhan; Gao, Lijuan; Zhang, Lan; Zhang, Yushan; Zhang, Xiaolin; Zhu, Lu; Zhang, Fan; Chen, Jing; Huang, Jinhua; et al.
Abstract: Keratinocytes regulate melanogenesis in a paracrine manner. Previous studies have shown that melatonin can directly inhibit melanin production in the melanocytes. However, it is unclear whether melatonin can also indirectly regulate melanogenesis through the keratinocytes. In this study, we explored the role of melatonin in regulating keratinocyte‐mediated melanogenesis using reconstructed human epidermis (RHE). Melatonin showed an inhibitory effect on melanin synthesis in this model. Furthermore, the conditioned media from melatonin‐treated HaCaT cells downregulated melanogenesis‐related genes, including MITF, TYR, TYRP1, DCT and RAB27A in the pigment MNT1 cells, and decreased levels of phosphorylated ERK, JNK and p38. RNA sequencing further showed that mitochondrial functions and oxidative stress pathway in the MNT1 cells were inhibited by the conditioned medium from melatonin‐treated HaCaT cells. Furthermore, melatonin reduced the secretion of ET‐1 and PTGS2 from HaCaT cells by inhibiting the JAK2/STAT3 signalling pathway. In conclusion, melatonin downregulates the paracrine factors ET‐1 and PTGS2 in the keratinocytes by inhibiting the JAK2/STAT3 pathway, which reduces melanin production in pigment cells. Thus, melatonin has a potential therapeutic effect on skin pigmentation disorders.